Ethics in the Visual Art of Sven Nordqvist - Smyczyńska, Katarzyna (Porównania, 2016)
The article „Ethical gaze: the visual art of Sven Nordqvist” discusses the relationship between the two characters in the artist’s Festus and Mercury books and the narrative role played in this context by the space in which they live. Nordqvist’s illustrations deconstruct common notions of childhood and adulthood and ironically expose conventionality and hierarchical order often accepted unquestioningly by adults. The artist’s characterisation of the protagonists puts special emphasis on their compassionate attitude and concern for the other. Nordqvist’s visual art thus becomes a continuation of Janusz Korczak’s educational philosophy.